Ecological apocalypticism in Ella Hickson's Oil, Lucy Kirkwood's The Children and Duncan Macmillan's Lungs - Andrew Burton (Janeway JS, 2021)
The vast spatio-temporal dimensions of global warming and ecological devastation are hyberobjects (Morton, 2013) which humans are able to compute but not directly see. This is problematic for dramatists and theatre makers whose work tends to focus on portraying more immediate emotions on a human scale. Diamond (2016) has written insightfully about a number of contemporary British plays which attempt to grapple with the “genre-bending” hyperobject of global warming, either by working within the limitations of conventional genres or by extending the boundaries of those genres. In this essay, I develop her theme by asking how dramaturgical form rather than genre may be harnessed in this task. I examine how Kirkwood exploits the naturalistic form in her play The Children to show the impacts of the hyperobject on the characters’ lives. I further examine how the open time, open place structure (pace Jeffreys, 2019) of Hickson’s reconfigured Brechtian epic Oil enables the playwright to connect human and ecological timescales. I explore how Macmillan has his dramaturgical cake and eats it by pioneering, in his play Lungs, a hybridised form which offers a highly affective audience experience, aligning human and more-than-human timescales. Finally, I theorise that playwrights and theatre makers might profitably experiment with such formal hybridisations in future attempts to dramatize the hyperobject’s ontological vastness.